Exploring the Enchanting Wings: A Comprehensive Study on Butterfly Diversity in the Eastern Ghats of Visakhapatnam District, Andhra Pradesh, India - Bhusala, Venkata Ramana; Saragada, Appanna; Surisetti, Ravi Babu (Indian Forester, 2024)
Butterflies are crucial indicators of biodiversity and environmental change, and are therefore important for ecological studies. This research focuses on butterfly diversity in the Eastern Ghats of the Visakhapatnam District, Andhra Pradesh, India, and was conducted from March 2014 to October 2021. A total of 190 butterfly species from 122 genera were recorded in six families, with the Nymphalidae family being the most dominant, followed by Lycaenidae, Hesperiidae, Pieridae, Papilionidae, and Riodinidae. Of these, 27 species are protected under the Indian Wildlife (Protection) Act, 1972; (As amended by Act No. 18 of 2022,w.e.f.1-4-2023), nine species are listed by the International Union for Conservation of Nature (IUCN); and one species, the common birdwing, is included in Appendix II of the Convention on the International Trade in Endangered Species (CITES). This study highlights the role of butterflies as pollinators and their sensitivity to environmental change, highlighting the need for conservation efforts. These results contribute to a better understanding of butterfly diversity in the region and highlight the importance of protecting their habitats for ecological balance.